Threat Perceptions in Europe: Domestic Terrorism and International Crime - Syed Mansoob Murshed (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This paper focuses on two areas of security concern for the European Union: terrorism and international crime. I present a model of game-theoretic interaction between a European state and a domestic dissident group, who, on occasion, may resort to acts of terrorism. Here, identity is crucial to the putative terrorist, providing the microfoundations of dissident group behaviour by solving the collective action problem. I also sketch a macromodel of drugs production in a conflict-ridden developing country, where I argue that demand-side policies of regulation may be better than policies that are aimed at eradicating supply. As far as the policy implications are concerned, first excessive deterrence against potential terrorists may backfire. Secondly, space needs to be created so that Muslim migrants are able to merge their personal identities within their adopted European homelands. Thirdly, the economic discrimination against Muslims in Europe needs to be redressed. Finally, aid to fragile drug producing states should be broad-based and poverty reducing, not just benefiting warlords.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: C72; D74; D81; F13; F35; H11; O19; 330; European Security; Conflict; Terrorism; Narcotics Trade